Pemanfaatan molase sebagai sumber karbon alternatif dalam pembuatan nata de coco - Budi Santosa; Wirawan Wirawan; Rikawanto Eko Muljawan (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
In the process, nata de coco is formed from the decomposition of carbon sources by Acetobacter xylinum by fermentation, converted into cellulose which was originally a thin membrane and then increasingly thickened forming nata pellicles. Making nata de coco has been utilizing carbon sources from sugar. The price of sugar in its development is increasingly expensive so it is necessary to find alternative carbon sources that are cheap one of which is molasses. The research aims to obtain the right concentration of molasses in producing high quality nata de coco. The research design used was a single complete Randomized Design (CRD), as a factor, namely the concentration of molasses consisting of 6 levels M1 = 1%, M2 = 1.5%, M3 = 2%, M4 = 2.5%, M5 = 3 %, M6 = 3.5%. The treatment was repeated 4 times so that the samples obtained were 24 samples. The results showed that molasses could be used as an alternative carbon source in making nata de coco. The concentration of molasses that produce quality nata de coco is 3% with a thickness of 1.98 cm, weight of 275 grams and crude fiber 2.95%. But the color of nata de coco produced is murky brown. Thus molasses can be used as a carbon source instead of sugar in the manufacture of nata de coco